Jurnal - Muhammad Reyhan Riyandito (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
The Kapasan Chinatown area has considerable potential to become a tourist destination that can attract tourists to visit. However, in reality, the number of tourist visits, both domestic and foreign, to the Kapasan Chinatown area is still very low when compared to other tourist attractions in Surabaya. For this reason, a tourism development strategy is needed to improve the quality of tourism destinations in the Kapasan Chinatown area. This study aims to find a strategic formulation for developing a tourist destination in the Kapasan Chinatown area by using a SWOT analysis tool. Kapasan's strengths, weaknesses, opportunities and threats as a long-standing tourist destination in Surabaya are analyzed comprehensively. From the results of the analysis, it can be seen that the Kapasan Chinatown area is seen as having low competitive power to face threats from tourist destinations